The Political Economy of a Publicly Provided Private Good with Adverse Selection - Sophia Delipalla; Owen O'Donnell (University of Kent, Department of Economics, 1999)
Given heterogeneity in incomes and health risks, with asymmetric information in the latter, preferences over the public-private mix in health insurance and care are derived. Results concerning crowding-out in the presence of adverse selection are established. For low-risk individuals, crowding-out depends on risk aversion. A set of such individuals prefers a mixed public-private health care system. A majority-voting equilibrium exists. Under weak assumptions about the income distribution and tax function, both public and private sectors exist in the equilibrium. Comparing information regimes, public provision is more likely to be positive, and will not be lower, under asymmetric information. In the presence of asymmetric information, the equilibrium is more complicated than the "ends-against-the-middle" variety derived elsewhere in the literature.
Keywords: D82; H42; H51; H11; 330; Public provision of private goods; health insurance; health care; adverse selection; public choice; Adverse Selektion; Krankenversicherung; Neue politische Ökonomie; Theorie